Smoking as Risk Factors to Dry Eye Syndrome - Faida, Soraya Nur; Zulaikhah, Siti Thomas; Pritasari, Alteriana Mydriati Sita (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2019)
Cigarette smoke can damage the fat layer of the tear film lperoxidation. Dry eye syndromeis a cluster of disorders caused by an imbalance between production and excretionof tears, causing symptoms of discomfort in the eye. This study aims to related riskfactors smoke of dry eye syndrome. Analytic observational with cross sectional design,population of all visitors, officers and employees KAI Poncol station Semarang. Sampleof 60 respondents who meet the inclusion and exclusion criteria. Data about dry eye syndrome are examined using Schirmer I test, data on smoking were taken using a checklist.The data obtained were analyzed using chi-square test. Results of the respondentswho smoke and have dry eye syndrome was higher (80.6%) compared with non-smokers(25.0%). The results chi-square test p=0.000 (p<0.05), PR = 3.222 (95%CI:1.582-6.562).Smoke who risk 3.222 times higher chance of developing dry eye syndrome comparedwith do not smoke.